Mutations in the DI–DII linker of the NDV fusion protein conferred hemagglutinin-neuraminidase-independent cell fusion promotion. (29th May 2019) - Chi, Miaomiao; Xie, Wenyan; Liu, Ying; Wen, Hongling; Zhao, Li; Song, Yanyan; Liu, Na; Chi, Lianli; Wang, Zhiyu
Abstract : Newcastle disease (ND), which is caused by Newcastle disease virus (NDV), is a highly contagious disease in chickens and is a great threat to the poultry industry. Fusion of the viral and target cell membranes is a prerequisite for NDV's entry into host cells. This process is directly mediated by the fusion (F) protein. Although several domains of F are known to regulate membrane fusion activity, the roles of the DI–DII linker (residues 376–381) of the NDV F protein in membrane fusion still remain unclear. To investigate the roles of this linker in NDV F-induced cell–cell fusion, mutations were engineered into this linker by site-directed mutagenesis. These mutants were analysed with respect to cell surface expression and membrane fusion activity. Each of the mutated F proteins in this linker was expressed at the cell surface at a similar level to wild-type (WT) F. However, most of them resulted in significant alterations in fusion activity. In particular, the mutants G377S, A378D, L379A and T380P were able to independently mediate cell fusion in the absence of HN protein in BHK-21 cells. Taken together, the results indicated that the DI–DII linker region has an important effect on the fusion activity of NDV F and mutants in this region could alter the requirement for HN for the promotion of membrane fusion.